Implementation of Social Media-Based Entrepreneurship in The Millenial Era for Students of IAIN Kediri - Nawan, Achmad Robith Saifun (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2018)
In this millennial era, there are many business people who have joined the online world and consumers are mostly looking for goods through the online so that in this case prospective entrepreneurs must compete in utilizing the mastery of technology and information. Therefore, IAIN Kediri students as a generation who are ready to compete in the business must have an interest in becoming entrepreneurs who have the ability in technology, especially social media. The problem that will be examined in this paper is the application of social media-based entrepreneurship in the millennial era to IAIN Kediri students, the syari'ah faculty. The purpose of this study is to find out how far students apply entrepreneurship by using social media. This research was carried out at IAIN Kediri. The sample of this study was 7 people with a purpose sampling. Data were collected directly from respondents using observation, interviews and documentation. The results of this study prove that students still lack of interest in entrepreneurship, students are still not optimal in mastering social media to implement entrepreneurship, entrepreneurial education is still less effective in terms of practice.